Analisis pengaruh Aplikasi Tiktok Terhadap Peningkatan Pembelajaran Bahasa Inggris Pada Siswa - Irianto, Sugeng; Al-Amin, Al-Amin (Universitas Pahlawan Tuanku Tambusai, 2021)
The development of information technology has entered 4.0 in Indonesia now, such as the tiktok application, this is good if taken from the positive side where tiktok is used as an English learning medium to improve student learning outcomes. The purpose of this study is to analyze the effect of the Tiktok application on improving students' English learning. This research method uses quantitative with descriptive analysis. The correspondent data is around 38 students who have the tiktok application. Samples were taken from students who were interviewed. The results of this study are that in this study the researchers concluded the analysis of the effect of the Tiktok application on improving English learning in students with the following analysis: Based on the ANOVA test, a significance level of probability was obtained. then the H0 hypothesis is rejected and the Ha hypothesis is accepted, which means that there is a significant influence on the Tiktok application on improving English learning in students.